2021
DOI: 10.1038/s41598-021-84350-2
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to mesenchymal transition and microRNA expression are associated with spindle and apocrine cell morphology in triple-negative breast cancer

Abstract: Triple negative breast cancers (TNBC) are a morphologically and genetically heterogeneous group of breast cancers with uncertain prediction of biological behavior and response to therapy. Epithelial to mesenchymal transition (EMT) is a dynamic process characterized by loss of typical epithelial phenotype and acquisition of mesenchymal characteristics. Aberrant activation of EMT can aggravate the prognosis of patients with cancer, however, the mechanisms of EMT and role of microRNAs (miRNAs) in EMT activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 79 publications
4
19
0
Order By: Relevance
“…The pathway analysis revealed that these miRNAs closely interfere with several important signaling pathways, such as Wnt, ErbB/HER2, and MAPK pathways; the authors also speculated that these miRNAs might contribute to EMT in special types of TNBC -apocrine and spindle cell (metaplastic) carcinomas, concluding that further mechanistic studies are essential to confirm their observations. 42 Notably, we also demonstrated the EMT in a case of morphologically apocrine DCIS (AR + ) harboring PTEN and HRAS mutations with progression to spindle cell metaplastic carcinoma that had the same mutational profile and a loss of AR expression. 43 EMT was supported by the loss of E-cadherin protein (without CDH1 gene mutations or loss) and nuclear ß-catenin expression in invasive spindle cell component.…”
Section: Epithelial-to-mesenchymal Transition (Emt) In Apocrine Carci...supporting
confidence: 54%
See 1 more Smart Citation
“…The pathway analysis revealed that these miRNAs closely interfere with several important signaling pathways, such as Wnt, ErbB/HER2, and MAPK pathways; the authors also speculated that these miRNAs might contribute to EMT in special types of TNBC -apocrine and spindle cell (metaplastic) carcinomas, concluding that further mechanistic studies are essential to confirm their observations. 42 Notably, we also demonstrated the EMT in a case of morphologically apocrine DCIS (AR + ) harboring PTEN and HRAS mutations with progression to spindle cell metaplastic carcinoma that had the same mutational profile and a loss of AR expression. 43 EMT was supported by the loss of E-cadherin protein (without CDH1 gene mutations or loss) and nuclear ß-catenin expression in invasive spindle cell component.…”
Section: Epithelial-to-mesenchymal Transition (Emt) In Apocrine Carci...supporting
confidence: 54%
“…41 miRNAs have been extensively characterized in various cancers, including breast cancer. Recently, Koleckova et al 42 demonstrated that triple-negative breast carcinomas with apocrine and spindle cell (metaplastic) morphology exhibited a distinct miRNA profile compared with other breast cancers. In particular, they showed the downregulation of hsa-miRNA-143-3p and hsa-miRNA-205-5p and upregulation of the hsa-miR-22-3p, hsa-miRNA-185-5p, and hsa-miR-4443 ( Table 2 ).…”
Section: Epithelial-to-mesenchymal Transition (Emt) In Apocrine Carci...mentioning
confidence: 99%
“…This suggests that miR-145-5p inhibits PC-3 cell metastasis and promotes PC-3 cell apoptosis. Moreover, the expression of hsa-miR-145-5p is also decreased in tumor transformational apocrine and spindle cells compared to in situ carcinoma or nonttumor structures [37]. This indicates that miR-145-5p has a potential regulatory effect on cancer metastasis.…”
Section: Discussionmentioning
confidence: 89%
“…During several steps of metastasis, the cancer cells disseminate into other organs via EMT. Furthermore, it is well known that miRNAs play a pivotal role in the regulation of EMT phenotype, also in OS cells [ 43 , 49 , 50 , 51 ]. Hence, we investigated the potential role of miR-CT3 in regulating expression of EMT-factors.…”
Section: Discussionmentioning
confidence: 99%